2017
DOI: 10.1038/srep41476
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Cardiotoxic Mechanism for a Pervasive Global Pollutant

Abstract: The Deepwater Horizon disaster drew global attention to the toxicity of crude oil and the potential for adverse health effects amongst marine life and spill responders in the northern Gulf of Mexico. The blowout released complex mixtures of polycyclic aromatic hydrocarbons (PAHs) into critical pelagic spawning habitats for tunas, billfishes, and other ecologically important top predators. Crude oil disrupts cardiac function and has been associated with heart malformations in developing fish. However, the preci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
117
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 135 publications
(139 citation statements)
references
References 56 publications
14
117
4
Order By: Relevance
“…In addition to the depressive effects on Ca 2+ cycling, Phe was found to affect membrane excitability by prolonging action potential duration (APD) by inhibiting K + efflux from the cardiomyocyte via the rapid delayed rectifier K + ‐current ( I Kr ) (Brette et al . , ), analogous to the original observations in zebrafish embryos (Incardona et al . ).…”
Section: Introductionsupporting
confidence: 82%
See 4 more Smart Citations
“…In addition to the depressive effects on Ca 2+ cycling, Phe was found to affect membrane excitability by prolonging action potential duration (APD) by inhibiting K + efflux from the cardiomyocyte via the rapid delayed rectifier K + ‐current ( I Kr ) (Brette et al . , ), analogous to the original observations in zebrafish embryos (Incardona et al . ).…”
Section: Introductionsupporting
confidence: 82%
“…Consistent with the in vivo whole‐heart effects observed in exposed fishes, these studies demonstrated that complex mixtures of crude oil, or Phe in isolation, altered both cellular Ca 2+ cycling and AP waveform (Brette et al . , ; see Fig. ).…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations